Development of a Web Application for Taking Tests by Blind People - Balaban, Tilbert; Sachenko, Anatoliy (Видавництво Львівської політехніки, 2023)
The main purpose of this article is to de- scribethe process of creating a web application designed specifically for blind individuals to take tests. The author discusses the challenges that visually impaired individuals face when taking tests and how the new web application addresses these challenges. The application has been devel- oped using web accessibility guidelines and includes features such as screen reader compatibility, speech recognition, keyboard navigation, and high-contrast options. The author also discusses the testing process used to ensure that the application was effective and accessible for visually impaired users. The results of the study indicate that the application was successful in providing an accessible platform for blind individuals to take tests. The article provides valuable in- sights for developers interested in creating accessible web applications for individuals with disabilities.
Keywords: accessibility; assistive technology; screen reader; speech recognition; user testing